Antimicrobial screening of Cichorium intybus seed extracts - Tauseef shaikh; Rukhsana A. Rub; S. Sasikumar (Arabian Journal of Chemistry, 2016)
Medicinal plants play an important role in the field of natural products and human health care system. Chemical constituents present in the various parts of the plants can resist to parasitic attack by using several defense mechanisms. One such mechanism is the synthesis of antimicrobial compound. Cichorium intybus is one of the important medicinal plants which belong to Asteraceae family. In the present work, antimicrobial screening of C. intybus seed extract was studied by agar well diffusion assay by using aqueous and organic extracts. The pathogenic microorganisms tested include Staphylococcus aureus, Pseudomonas aeruginosa, Candida albicans and Escherichia coli. All the seed extracts showed antimicrobial activity against tested microorganisms whereas S. aureus was found to be most sensitive against aqueous extract and had the widest zone of inhibition. Ethyl acetate and ethanol extract were found to be significant against P. aeruginosa and S. aureus. The results obtained from antimicrobial screening scientifically support the effectiveness of the medicinal plant.